P217 Serum metabolic profile of creatine correlates with repeated motor evoked potentials: A study on TMS-induced repetition suppression. Issue 9 (September 2017) - Kallioniemi, Elisa; Kärkkäinen, Olli; Määttä, Sara; Könönen, Mervi; Kivimäki, Petri; Kaarre, Outi; Kekkonen, Virve; Laukkanen, Eila; Tolmunen, Tommi
Abstract : Objectives: The motor evoked potentials (MEPs) induced by transcranial magnetic stimulation (TMS) mainly reflect the electrophysiological characteristics of the motor system. Although the MEP amplitude is a peripheral response, it can be applied to study several neural phenomena, such as repetition suppression (RS). In RS, a train of TMS pulses is repeated and the induced MEP amplitudes suppress after the first MEP. RS is suggested to be a general response of the brain to repeated stimuli. When measuring the RS, the peripheral muscles contract frequently and thereby in this study, we evaluated whether RS is influenced by the muscle metabolism. Methods: The metabolic profiles of 73 subjects (37 females) were measured from serum samples and TMS was targeted on the cortical representation of the right abductor pollicis brevis muscle on the primary motor cortex. The RS protocol included repeating trains of 4 pulses at 110% of the resting motor threshold with a 1s inter-stimulus interval and 20s inter-train interval. Results: Serum creatine levels were found to correlate negatively with the magnitude of RS ( r = −0.43, p = 0.0002). Discussion: Creatine is an important metabolite relating to energy requiring situations in the muscles. Therefore, the results suggest that large amounts of fast energy reservoir may be needed to keep up the muscle contraction in response to repeated TMS pulses. Conclusions: Subjects with different metabolic profiles of creatine responded differently to repeated TMS pulses. Significance: The possible influence of different individual metabolic profiles on repeated MEPs should be taken into account in TMS motor paradigms involving pulse repetition.